International developments in investigative interviewing - Bull, Ray (Springer, 2014)
Between news stories of coerced confessions and the over-the-top interrogations shown in crime dramas, there seems to be no end of wrong ways to question suspects. And as wrong as these methods are, they are equally counterproductive when the resulting statements are based on questioners' assumptions rather than the truth. The expert pages of Investigative Interviewing model an approach that reflects an ethical base emphasizing persuasion rather than coercion as well as the evidence base. International in scope, this innovative volume reflects sophisticated new interview methods and often surprising findings on the psychology of suspects, victims, witnesses, and law enforcement personnel. Topics cross criminal justice settings and contexts, such as when information should be disclosed to suspects, how interviews are conducted in international tribunals, and the emerging concept of human intelligence interviewing. Taken together, these chapters are a leading-edge guide to obtaining statements that stand up as reliable evidence. Included in the coverage: Investigative interviewing of sex offenders. Psychological processes underlying true and false confessions. Between investigator and suspect: the role of the working alliance in investigative interviewing. A training program for investigative interviewing of children. A systematic review of different types of consistency in truth tellers and liars. Prosecutors perceptions on improving child witness interviews about abuse. Suited to the researcher and the educator as well as the frontline professional, Investigative Interviewing heralds a major advance in forensics: education and training programs rooted in best practices for more effective interviewing--and consigning excessive interrogations to the fiction writers.